Use of a Fibrin Sealant Patch at Cesarean for Conservative Management of Morbidly Adherent Placenta - Greenberg, James A.; Robinson, Julian N.; Carabuena, Jean M.; Farber, Michaela K.; Carusi, Daniela A. (American Journal of Perinatology Reports, 2018)
Background Morbidly adherent placenta represents a surgical challenge and source of maternal morbidity and mortality. We report the use of a fibrin sealant patch to address hemorrhage associated with a morbidly adherent placenta during cesarean delivery.Case A patient underwent repeat cesarean delivery with complete anterior placenta previa and anticipated morbidly adherent placenta. Bleeding persisted following delivery and removal of the placenta, despite uterine artery embolization. A fibrin sealant patch was applied as an adjuvant intervention to the placental bed and hemostasis was achieved without resorting to a hysterectomy.Conclusion Postpartum hemorrhage is an ongoing leading source of maternal morbidity and mortality. A case is presented in which a fibrin sealant patch provided control of focal placental bed bleeding, allowing removal of a focal morbidly adherent placenta and avoidance of hysterectomy.
Keywords: fibrin patch; placenta accrete; morbidly adherent placenta; postpartum hemorrhage; cesarean